(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article describes the condition of phimosis in children under 3 years of age and its clinical significance. Phimosis is a condition characterized by incomplete closure of the foreskin by the skin layer of the foreskin, which is often considered a physiological process. However, in some cases, it can take a pathological form and cause dysuria, a tendency to recurrent infections, and painful conditions in the child. The article analyzes the main clinical indicators, diagnostic methods, and individual approach to the selection of treatment tactics in young children. The main attention is paid to conservative methods - compliance with hygiene, the use of local medicines, and the effectiveness of special exercises. Also, conclusions are given about the need for a surgical method - circumcision, and the importance of its correct timing. The results of the study indicate the need for an individual and comprehensive approach to the treatment of phimosis in children under 3 years of age.